ACCOUNTABILITY: IMPACT ON HOSPITAL INFECTION CONTROL (Cadernos ESP, 2024)
Infections related to healthcare are identified as one of the greatest risks of negative impact on public health, causing prolonged hospitalization of patients, increasing hospital costs, and it is essential to think about strategies to prevent such events. The descriptive study seeks to report the experience of a public hospital, on a strategy called Accountability of infections, applied by the hospital infection control service team, from January 2022 to August 2023. The instrument used is analysis of Documentary collection based on available spreadsheets and reports. In the intervention, strategies and actions were created to encourage the participation of professionals in the management process of patient care, involving managers and teams, reducing the density of infections by 40% and increasing adherence to hand hygiene among professionals, reaching an average of 93% in 2023 strengthening the patient safety culture.
Keywords: Prevention; Infection; Hand Hygiene